Limit laws for arithmetic functions of J. P. Kubilius class H, defined on the set of „shifted“ primes - Barban, M. B.; Vinogradov, A. I.; Levin, B. V. (Lithuanian Mathematical Journal, 1965)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: М. Б. Барбан, А. И. Виноградов, Б. В. Левин. Предельные законы для функций класса Н И. П. Кубилюса, заданных на множестве «сдвинутых» простых чисел M. B. Barbanas, A. I. Vinogradovas, B. V. Levinas. Ribiniai dėsniai J. Kubiliaus klasės H funkcijoms, definuotoms „pastumtų“ pirminių skaičių aibėje